Transfer matrix model and experimental validation for a radial-torsional ultrasonic motor. (November 2021) - Wang, Le; Wang, Liang; Lin, Yuyang; Lu, Xiaolong; Zhao, Chunsheng
Highlights: An electromechanical model utilizing the transfer matrix method is built to analyze the dynamic behavior of the radial-torsional motor. This transfer matrix model of the system could provide an effective approach for simulating the coupled mechanical and electrical properties. The calculated vibration characteristics of the prototype motor is validated by using a 3D laser Doppler vibrometer. The proposed transfer matrix method opens a new avenue to effectively evaluate the mechanical performance of mode conversion ultrasonic motors. Abstract: Traditional traveling-wave rotary ultrasonic motors have been widely used in many applications due to their excellent output performances. However, the structure optimization have be hindered by the specific requirements on the piezoelectric ceramics with complex polarizations and shapes. To address such issues, a compact type ultrasonic motor operating at radial-torsional conversion mode is proposed in this paper, which is simply excited by one ring type piezoelectric wafer with a single polarization. This motor basically consists of one rotor and one disk type stator, which can be divided into an outer ring, four connection beams and an inner ring. A ring type piezoelectric wafer is bonded to the bottom face of the outer ring. Upon an excitation signal at resonance frequency, the proposed motor is able to rotate, driven by the torsional vibration mode of the inner ring converted from the radial vibration mode of the outer ring via the connecting beams An electromechanical model utilizing the transfer matrix method is built to analyze the dynamic behavior of the motor. This transfer matrix model of the system could provide an effective approach for simulating the coupled mechanical and electrical properties. Based on the proposed model, the dynamic process for converting the radial vibration mode into the torsional mode is quantatively assessed. Last, the vibration characteristics of the prototype motor is tested by using a 3D laser Doppler vibrometer and the experimental results are in good agreement with the calculations, confirming the validity of the transfer matrix model and the feasibility of the motor design.